The modulation of gut microbiota by herbal medicine to alleviate diabetic kidney disease – A review - Du, Jinxin; Yang, Meina; Zhang, Zhongwen; Cao, Baorui; Wang, Zhiying; Han, Jinxiang (Frontiers in Pharmacology, 2022)
The treatment of diabetic kidney disease (DKD) has been the key concern of the medical community. Herbal medicine has been reported to alleviate intestinal dysbiosis, promote the excretion of toxic metabolites, and reduce the secretion of uremic toxins. However, the current understanding of the modulation of the gut microbiota by herbal medicine to delay the progression of DKD is still insufficient. Consequently, we reviewed the knowledge based on peer-reviewed English-language journals regarding regulating gut microbiota by herbal medicines in DKD. It was found that herbal medicine or their natural extracts may have the following effects: modulating the composition of intestinal flora, particularly Akkermansia, Lactobacillus, and Bacteroidetes, as well as adjusting the F/B ratio; increasing the production of SCFAs and restoring the intestinal barrier; reducing the concentration of uremic toxins (p-cresol sulfate, indole sulfate, TMAO); inhibiting inflammation and oxidative stress.